2006
DOI: 10.1002/lt.20740
|View full text |Cite
|
Sign up to set email alerts
|

Biliary strictures in living donor liver transplantation: Incidence, management, and technical evolution

Abstract: Biliary complications, biliary strictures (BS) in particular, continue to be a significant cause of morbidity after LDLT despite technical refinement. In this study, we assessed the incidence of BS and their management in living donor liver transplantation (LDLT) with special reference to the type of biliary reconstruction. A total of 182 LDLTs performed at our institution for either adult (n ‫؍‬ 157) or pediatric (n ‫؍‬ 25) patients were included in the study. The duct-to-duct (DD) biliary reconstruction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 25 publications
2
92
1
6
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12].8% in studies published after 2008 (Table 6). [27][28][29][30][31][32][33][34] Overall biliary complications in LDLT in our series was seen in three recipients (16.6%) which compares well with other studies. Aberrant biliary anatomy or two or more ducts have been proved to be a significant risk factor for the development of biliary complications.…”
Section: Biliary Complicationssupporting
confidence: 90%
“…[3][4][5][6][7][8][9][10][11][12].8% in studies published after 2008 (Table 6). [27][28][29][30][31][32][33][34] Overall biliary complications in LDLT in our series was seen in three recipients (16.6%) which compares well with other studies. Aberrant biliary anatomy or two or more ducts have been proved to be a significant risk factor for the development of biliary complications.…”
Section: Biliary Complicationssupporting
confidence: 90%
“…While identification of the causative factors of biliary complications and subsequent refinements in reconstruction techniques might reduce the incidence of these complications in some institutions [20][21][22], the rate of biliary complications, particularly biliary strictures, does not seem to significantly decrease with experience [7,8,19,23]. Kyoto University divided LDLT recipients into three groups according to case experience (Group 1, cases 1-100; Group 2, cases 101-200; and Group 3, cases 201-335), and found that while the rate of bile leakage significantly decreased with experience (25% in Group 1, 14% in Group 2, and 13% in Group 3, p = 0.021), there were no differences in the development of biliary strictures among the three groups (19,28, 26%, respectively, p = 0.290) [7].…”
Section: Incidence and Risk Factors Of Biliary Strictures After Ldltmentioning
confidence: 99%
“…The increased use of split livers in the United States and Europe also contributed to the surgical skills needed to successfully perform the LDLT procedure. Unlike living donor kidney transplantation, where advantages of living donor over deceased donor grafts have been demonstrated in both recipient and graft survival, and where the safety of the donor operation has been documented, LDLT is still under a high level of scrutiny [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%